Novel mitochondrial-targeted thiadiazolo[3, 4-g]quinoxaline dyes as efficient photosensitizers for ultra-low dose operable photodynamic therapy. Issue 76 (4th September 2019) - Li, Xianqiang; Zhang, Li-Peng; Kang, Lin; Zhao, Yuxia
Abstract : Two novel thiadiazolo[3, 4- g ]quinoxaline based PSs (TQs-3 andTQs-4 ) were designed and synthesized.TQs-4 based nanoparticles exhibited outstanding PDT efficacies towards three tumor cell lines, showing a promising potential for PDT application. Abstract : Two novel thiadiazolo[3, 4- g ]quinoxaline (TQ) photosensitizers (PSs), TQs-3 andTQs-4, were designed and synthesized. Both of them presented ultra-high singlet oxygen quantum yields under red light irradiation. By carrying out in vitro photodynamic therapy (PDT) experiments usingTQs-4 loaded nanoparticles (TQs-4 NPs ) to treat three kinds of tumor cell lines: 4T1, HeLa and MCF-7 cells, it was demonstrated thatTQs-4 NPs had outstanding PDT efficacies. An ultra-low dose ofTQs-4 (0.14 μg mL −1 ) can realize the death of more than 90% HeLa cells (635 nm, 60 mW cm −2, 10 min), which indicated thatTQs-4 show promising potential as a novel PS for PDT applications.